(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to improve underhand passing skills in volleyball games through the 3-3 game approach method for seventh-grade students of SMP Negeri 13 Palembang. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model, which is implemented in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. Data were collected through underhand passing skills tests, student activity observations, and activity documentation. The results showed a significant increase in students’ underhand passing skills. The percentage of learning completion increased from 32% in the initial observation to 68% in cycle I, and finally reached 84% in cycle II. These findings indicate that the 3 on 3 game approach method is effective in improving students’ underhand passing skills.